Studies on Management of Natural Bamboo (Dendrocalamus strictus Nees) in Shiwalik Hills of Haryana State, India - Ramesh Singh, D. R. (Indian Forester, 2002)
Fast growing, giant perennial grasses with woody fibre-bamboos are getting re-discovered. India has 135 species of bamboos growing over 8.9 million ha of natural forests, three species contribute to 80 % of above coverage.Dendrocalamus strictus Nees occupies 45% of total bamboo forests. It grows naturally in three districts of State of Haryana,India. Departmental harvesting operations and sale practised for eight years was studied as efforts are being made to grow bamboo under agroforestry. At present there are only two species viz., Eucalyptus tereticornis Smith and Populus deltoides Marsh grown extensively under agroforestry plantations leading to monoculture-like situation, diversification of species is an urgent need. Studies have shown bamboo forests of Haryana currently yield 0.6 tonnes of freshly cut bamboos per ha. Harvesting expenses are Rs.10,000/ha. Gross and net return of Rs. 12,000 and Rs.2,000 respectively is obtained. When land rent is deducted net return is Rs.700/ha, giving a return of 12%. Either felling expenditure is to be reduced to Rs.5,000/ha or production of bamboo is to be increased to minimum of 1 tonne/ha so as to earn 25% returns to justify investment made. Piling of earth on clumps and in situ water harvesting has proved useful in increasing yields elsewhere can be tried in natural forests but chemical fertilizer application may be avoided. Bamboos grown in well-drained plains are highly productive under assured irrigation and fertilizer application. After first six years, farmers can harvest bamboo every year. Three times the level of harvests made from natural forests have been obtained in experimental plots and exceptionally good ones have exceeded 2 tonnes/ha.